Trophic relationships of hake (Merluccius capensis Castelnau, 1851 and M. paradoxus Franca 1960) from the Northern Benguela current ecosystem (Namibia) : inferences from stable isotopes and fatty acids - Iitembu, Johannes Angala (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Two species of hake (Merluccius capensis and Merluccius paradoxus) account for most of Namibia's fisheries catch, and they are important secondary consumers in the Benguela Current ecosystem. Inferences on their trophic relationships have been based mainly on stomach content analyses. However, such data are limited temporally because they represent only snapshots of recent feeding, and are quantitatively biased because of variation in the digestion rates of different prey. The principal aim of the thesis was to understand the trophic relationships of two hake species relative to each other, their known prey and top predators (demersal sharks) in the northern Benguela Current ecosystem (Namibia), using time-integrating trophic biomarkers. By using stable isotope (carbon and nitrogen) and fatty acid signatures of their muscle tissues, my overall objectives were to produce new knowledge about 1) hake ontogenic trophic relationships, 2) the contributions of different prey to hake diets, 3) hake dietary differences, and 4) some aspects of hake's trophic relationships with demersal sharks. Tissues of hake (n=358), their potential prey (n=455), and demersal sharks (n=42) were collected between 2008 and 2012 during demersal bottom trawl surveys off Namibia, for stable isotope and fatty acid analyses. And more...
Keywords: Hake -- Benguela Current; Merlucciidae -- Benguela Current; Multitrophic interactions (Ecology); Food chains (Ecology); Biotic communities -- Benguela Current; Merlucciidae -- Food; Fishery management -- Namibia; Stable isotopes; Fatty acids